2004
DOI: 10.1074/jbc.m410583200
|View full text |Cite
|
Sign up to set email alerts
|

The Poxvirus p28 Virulence Factor Is an E3 Ubiquitin Ligase

Abstract: A majority of the orthopoxviruses, including the variola virus that causes the dreaded smallpox disease, encode a highly conserved 28-kDa protein with a classic RING finger sequence motif (C 3 HC 4 ) at their carboxylterminal domains. The RING domain of p28 has been shown to be a critical determinant of viral virulence for the ectromelia virus (mousepox virus) in a murine infection model (Senkevich, T. G., Koonin, E. V., and Buller, R. M. (1994) Virology 198, 118 -128). Here, we demonstrate that the p28 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…Similarly, the RING-finger proteins MBP-IAP2, IE2, and PE38 of Bombyx mori nucleopolyhedrovirus (BmNPV) are able to reconstitute ubiquitination activity in vitro and their activity is dependent on their RING-finger motif [110]. Interestingly, Huang et al [111] demonstrated that the p28 proteins encoded by the ectromelia virus and the variola virus possess E3 ubiquitin ligase activity in biochemical assays as well as in cultured mammalian cells. Point mutations disrupting the RING-finger domain of p28 completely abolish its E3 ligase activity.…”
Section: Pathogen-derived Proteins Act As E3 Ligases In Host Cellsmentioning
confidence: 99%
“…Similarly, the RING-finger proteins MBP-IAP2, IE2, and PE38 of Bombyx mori nucleopolyhedrovirus (BmNPV) are able to reconstitute ubiquitination activity in vitro and their activity is dependent on their RING-finger motif [110]. Interestingly, Huang et al [111] demonstrated that the p28 proteins encoded by the ectromelia virus and the variola virus possess E3 ubiquitin ligase activity in biochemical assays as well as in cultured mammalian cells. Point mutations disrupting the RING-finger domain of p28 completely abolish its E3 ligase activity.…”
Section: Pathogen-derived Proteins Act As E3 Ligases In Host Cellsmentioning
confidence: 99%
“…It remains unclear whether HCV core induces proteosome-mediated core11 degradation. However, there is growing evidence that proteosome activity may be directed by a diverse range of viral proteins as part of an efficient viral propagation strategy (61)(62)(63)(64)(65)(66)(67). Indeed, it was recently reported that the core protein of HBV stimulates the proteasome-mediated degradation of the HBV X protein (HBX), when the HBV viral proteins, which are transcriptionally transactivated by the X protein, reach a sufficiently high levels for viral replication (68)(69)(70)(71)(72).…”
Section: Biochemical Properties Of Core11 Proteinsmentioning
confidence: 99%
“…The sequence of oligonucleotides 16615 (with 5Ј-FAM) and 13657 is 5Ј-CUAGCACGAACU UGUUUACCCUCCC-3Ј. FLAG-and His-tagged wild-type Ub as well as various K to R mutants of Ub were expressed and purified from Escherichia coli as described by Huang et al (41).…”
Section: Reagentsmentioning
confidence: 99%